2008
DOI: 10.1021/ja8058342
|View full text |Cite
|
Sign up to set email alerts
|

Cu(I)-Catalyzed Regioselective Synthesis of Polysubstituted Furans from Propargylic Esters via Postulated (2-Furyl)carbene Complexes

Abstract: Polysubstituted furan derivatives are regioselective obtained from (bis-alkynyl)methyl carboxylates in the presence of catalytic amounts of copper(I) salts. This multistep process is consistent with the intermediacy of a copper(I) (2-furyl)carbene complex which is intercepted by suitable trapping reagents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(36 citation statements)
references
References 23 publications
0
35
0
1
Order By: Relevance
“…The initial isomerization of the propargylic substrate 6 to the (E)-Knoevenagel intermediate IV then undergoes a 5-exo-dig cyclization to generate the putative 2-furyl copper(I) carbene species V, as already reported. [9] Now, the carbenoid nature of V is strongly supported as it cyclopropanates substrate 1 leading to the cyclopropyldiazo intermediate VI, which in turn undergoes the metal-catalyzed ring expansion to the final cyclobutene 7. As in the case of the PMP-substituted diazo substrates 2 (Table 1 and Scheme 1), the furyl substituent in VI perfectly controls the regioselectivity affording a single cyclobutene.…”
Section: Methodsmentioning
confidence: 99%
“…The initial isomerization of the propargylic substrate 6 to the (E)-Knoevenagel intermediate IV then undergoes a 5-exo-dig cyclization to generate the putative 2-furyl copper(I) carbene species V, as already reported. [9] Now, the carbenoid nature of V is strongly supported as it cyclopropanates substrate 1 leading to the cyclopropyldiazo intermediate VI, which in turn undergoes the metal-catalyzed ring expansion to the final cyclobutene 7. As in the case of the PMP-substituted diazo substrates 2 (Table 1 and Scheme 1), the furyl substituent in VI perfectly controls the regioselectivity affording a single cyclobutene.…”
Section: Methodsmentioning
confidence: 99%
“…237 The reaction was presumed to proceed through formation of a copper carbene intermediate following cyclization. When the reaction was carried out under air, moderate yields of the oxidized 2-acylfuran products were formed (Scheme 83).…”
Section: Reactions Of Hydrocarbonsmentioning
confidence: 99%
“…91 The reaction required Barluenga and co-workers have shown that bis-propargylic esters rearrange to enynones upon addition of Cu(I) catalysts, which subsequently cycloisomerize to copper(I) 2-furylcarbene complexes (Scheme 38). 92 These complexes react with silanes and germanes to generate furans in very good yields. The copper carbene intermediates can also be oxidized by air to generate ketones or reacted with ethyl diazoacetate to form alkenes.…”
Section: Scheme 36mentioning
confidence: 99%